A solution to improve the resolution: a comprehensive review of optical coherence tomography in coronary interventions - Sharma, Saksham; Ramnath, Parameswaran; Chintala, Deepthi; Mishra, Pragya; Siddique, Mazain; Sujana, Chitturi Sai; Bhardwaj, Shreyashi (International Journal of Research in Medical Sciences, 2026)
Intracoronary imaging, specifically optical coherence tomography (OCT) and intravascular ultrasound (IVUS), has become critical for optimizing percutaneous coronary intervention (PCI). OCT offers higher resolution than IVUS, allowing detailed assessment of vessel structure, plaque characteristics, and stent deployment. This review synthesizes current evidence regarding the procedural safety, stent optimization efficacy, and clinical utility of OCT compared to IVUS and conventional angiography. A narrative review was conducted following SANRA guidelines, utilizing searches of PubMed/MEDLINE and Google Scholar for studies published from 2015 to 2025. Eligibility criteria included RCTs, cohort studies, systematic reviews, and meta-analyses comparing OCT, IVUS, and angiography in adult patients undergoing coronary interventions, focusing on procedural safety, stent optimization (expansion, apposition, restenosis), and plaque assessment. CT-guided PCI demonstrated a superior safety profile compared to angiography-guided PCI, with significantly lower rates of in-hospital major adverse cardiovascular events (MACE) and all-cause mortality. OCT's high resolution enabled superior detection of critical optimization parameters, including stent malposition, which was detected in 39% of lesions by OCT versus only 14% by IVUS. OCT provides unique diagnostic capability for ACS by precisely identifying high-risk plaque features, such as thin-cap fibroatheromas. In stable CAD, OCT changes the procedural strategy in up to 50% of cases by guiding lesion preparation and stent sizing OCT is a safe and highly effective imaging modality for guiding PCI. Its superior resolution provides distinct advantages over IVUS and angiography, particularly in quantifying stent apposition and characterizing vulnerable plaques. While IVUS offers greater penetration depth, the combined evidence supports the use of OCT as a first-line intracoronary imaging tool to improve clinical outcomes, justifying the push toward the integration of both modalities for comprehensive plaque assessment.